Effects of grazing and fire management on rangeland soil and biocrust microbiomes - Maria V. Vega-Cofre; Wendy Williams; Young Song; Susanne Schmidt; Paul G. Dennis (Ecological Indicators, 2023)
Biocrusts play important roles in rangeland ecosystems by protecting soil surfaces and fixing carbon and nitrogen. Their responses to rangeland management practices, however, are poorly understood. Here, we characterised the impacts of cattle grazing and fire management (controlled 2- or 4-yearly burning versus no fire) on the diversity and composition of biocrust and associated soil bacterial communities (0–1 cm depth) in a long-term (30–60 years) field experiment in the Northern Territory, Australia. Both experiments were replicated on two soil types (vertosol, calcarosol). For the grazing experiment, we also characterised samples from 0 to 10 cm depth. Significant effects of grazing on bacterial community composition were only detected in the vertosol, where it was generally associated with enrichments of cyanobacterial taxa in the 0–1 cm samples, and more varied responses in 0–10 cm samples. In contrast, despite some minor reductions in the relative abundances of Bacillus populations in more frequently burned sites (late season 2-yearly burning), we did not observe any significant impacts of fire management on the overall composition of bacterial communities. Our findings indicate that the presence of livestock in rangelands increases the proportional representation of cyanobacteria within biocrust and associated soil microbiomes, and that these communities, at least from a taxonomic perspective, are not strongly impacted by fire management.